Filsafat Pendidikan Islam; Studi Filosofis Atas Tujuan dan Metode Pendidikan Islam - Rohinah (Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2013)
The Islamic view of human beings and life is formed by the harmony principle and the combination of senses, minds, and hearts of the faithful. The third harmony is the most fundamental epistemological base in Islamic philosophy. Thinking with full comprehension is intended as an instrument or tool in conducting research based on the epistemological framework. Thinking activity is regarded as a sacred duty in Islam, and thinking is a tool to deliver a progressive life, which is formed by absorbing the values of reality. Islamic education should be a process that is able to produce “Insan Kamil” to maximize his full potential. The methods of education should commonly reflect the condition of integrative – interconnective that is capable to stimulate the development of maximum potency.